THE EFFECT OF COMPENSATION AND ORGANIZATIONAL COMMITMENT TO WORK DISCIPLINE WITH JOB SATISFACTION AS INTERVENING VARIABLES IN SAKINAH WEDDING ORGANIZER - Mailani Rabiulkhri; Zunaidah; Agustina Hanafi; Badia Perizade (Fakultas Ekonomi Universitas Negeri Jakarta, 2019)
Wedding Organizer Business still needs human resources in carrying out its activities, therefore it is necessary to study how the influence of Organizational Compensation and Commitment which is owned by employees. This study had a population of 101 using the census method and 101 people who became respondents through the distribution of questionnaires were conducted on Sakinah Wedding Organizer employees. The effect of Compensation on Work Discipline through Job Satisfaction has positive and significant results, and the influence of Organizational Commitment to Work Discipline through Job Satisfaction has positive and significant results. Compensation is expected to be able to increase salaries and wages of employees properly so that employees feel satisfied and will be more disciplined in carrying out tasks. Organizational Commitment of employees is expected to have more attitude towards the company to make a good contribution to advance the company. Work Discipline Employees are expected to be able to comply with company regulations, including carrying out the tasks assigned by the provisions to be completed on time. Job Satisfaction Employees are expected to be able to conduct supervision and employee relations with superiors to create a good work environment.